Pengaruh PENGARUH PENDIDIKAN DAN INFLASI TERHADAP TINGKAT PENGANGGURAN DI PROVINSI RIAU TAHUN 2009-2023 - Depari, Brian Arpenta; Yulyanti, Sinta (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of education and inflation on the open unemployment rate in Riau Province from 2009 to 2023. This research applies a quantitative approach using time series data obtained from the Central Statistics Agency (BPS) of Riau Province. The analytical method used is multiple linear regression to determine both partial and simultaneous effects of the independent variables on unemployment. The results of the t-test indicate that education has a negative and highly significant effect on the open unemployment rate, meaning that an improvement in educational attainment contributes to a reduction in unemployment. Inflation also shows a negative and significant effect, suggesting that increases in inflation within a reasonable range are associated with higher labor absorption. Furthermore, the F-test results demonstrate that education and inflation simultaneously have a significant influence on the unemployment rate. The model is supported by an R-Squared value of 0.748, indicating that 74.8% of the variation in unemployment can be explained by the variables included in the model. These findings highlight the importance of improving educational quality and maintaining stable macro economic conditions to reduce unemployment in Riau Province.